2015
DOI: 10.1007/s00402-015-2334-3
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of subscapularis and shoulder function following arthroscopic treatment of isolated anterior and combined anterosuperior rotator cuff lesions

Abstract: Reconstruction of subscapularis lesions cannot provide full subscapularis function since a residual subscapularis insufficiency remains, other than in patients with small partial tears treated with debridement alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
1
12
0
1
Order By: Relevance
“…Furthermore, we compared the clinical outcomes in both groups using ASES and SST scores, unlike previous similar studies that used only the Constant score. 15,17,29 Finally, the unique findings of this study are the optimal cutoff values for the risk of retear of the repaired SSC in terms of tear dimensions, which have not been reported previously.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Furthermore, we compared the clinical outcomes in both groups using ASES and SST scores, unlike previous similar studies that used only the Constant score. 15,17,29 Finally, the unique findings of this study are the optimal cutoff values for the risk of retear of the repaired SSC in terms of tear dimensions, which have not been reported previously.…”
Section: Discussionmentioning
confidence: 48%
“…Tear characteristics in terms of tear retraction and superoinferior tear dimensions were worse in the isolated SSC group in the present study. In contrast, Gerhardt et al 17 reported that only a small number of patients with isolated SSC RCTs showed complete rupture of the SSC tendon (10.0%) compared with patients who had combined AS RCTs (22.9%). However, unlike our study, Gerhardt et al included patients with partial-thickness SSC tears for whom debridement was performed, which may have led to the difference in findings.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A significant association was found between the pattern of the tear (isolated or combined subscapularis), and the mean Constant-Dif, unlike Gerhardt et al and Miškulin et al [35,36]. The clinical improvement was greater in the C-STT group than in the I-STT group.…”
Section: Discussionmentioning
confidence: 75%
“…[4][5][6][7][8][9] 그동안 다른 회전근개에 비하여 견갑하건의 파열 빈도는 상당 히 낮은 것으로 보고되고 있었으며 이학적 검사로도 파열을 특이 적으로 구분하여 진단하기 어려운 점이 있어 그 임상적 중요도에 비해 간과된 경향이 있으나 최근 어깨관절에서 관절내시경을 이 용한 수술적 적용의 증가로 인하여 견갑하건의 파열, 특히 건 상 부에서의 관절면 측 부분 파열이 보다 많은 빈도로 관찰되면서 재조명되고 있다. [10][11][12][13] 현재까지는 견갑하건을 포함한 회전근개의 평가를 위한 검사 로는 여전히 자기공명영상이 표준적인 영상의학적 검사로 자리 잡고 있다. [14][15][16] 이후 변환기를 90도 회전시키면서 견갑하건에 대해서는 단축 Figure 1.…”
unclassified